Maxillary calcifying epithelial odontogenic tumor - P R Bindhu; Rekha Krishnapillai; Priya Thomas (Wolters Kluwer Medknow Publications, 2020)
Calcifying epithelial odontogenic tumor (CEOT) is a rare benign epithelial odontogenic tumor, having characteristic clinical and histopathological features. CEOT usually affects middle-aged adults without any gender predilection. Most of these cases are intraosseous and appear predominantly in the mandibular posterior region. It is not commonly found in the maxillary region; however, if appear, it can easily involve the surrounding areas including the maxillary sinus. Here, we discuss a case of CEOT in the maxillary premolar-molar region, the common site being the posterior mandible.